CO-PRINCIPAL DALAM PENGEMBANGAN LEMBAGA PENDIDIKAN DI SMP ISLAM NGADIREJO - Najib Mubarok; Muhamad Husnan; Della Oktavia; Najwa Elok; Muhamad Fatah; Ahmad Afa Al-Azman; Farid Setiawan Jodi; Husna Nashihin (At Turots: Jurnal Pendidikan Islam, 2024)
The aim of this research is to determine the implementation of the Co-principal leadership model in the development of educational institutions at Ngadirejo Islamic Middle School. This type of research is qualitative research using a case study approach through several stages, namely selecting themes, reading literature, problem formulation, data collection, data processing and analysis, theorizing, triangulation and drawing conclusions. The research subjects were 4 teaching and educational staff at Ngadirejo Islamic Middle School, namely the principal, deputy principal, administration coordinator and curriculum coordinator. Data collection techniques are carried out through observation, interviews and documentation. Data analysis was carried out through several stages, namely data reduction, data presentation and drawing conclusions. The research conducted shows that the implementation of the Co-principal leadership model at Ngadirejo Islamic Middle School is carried out by dividing the roles between the principal and deputy principal, both of whom collaborate with each other, especially in the development of educational institutions where the principal is responsible for the quality of education while the deputy principal is responsible for educational facilities. Overall, collaboration is carried out in curriculum development, teaching and education staff, infrastructure, finance, school administration and services, students and learning programs and community relations.